Rainfed assessment of foxtail millet (Setaria italica L. beauv) germplasms through genotyping and principal component analysis - Singh, Divya; Lawrence, Kapil; Marker, Shailesh; Bhattacharjee, Indranil; Lawrence, Reena; Choudhary, Ravish; Ercisli, Sezai; Karunakaran, Rohini (Frontiers in Plant Science, 2023)
Foxtail millet (Setaria italica (L.) beauv) are important crop underdeveloped countries, however, yield levels are low. The use of varied germplasm in a breeding approach is critical for increasing productivity. It can be cultivated effectively in a wide range of environmental circumstances, but it is best suited to hot and dry climates. In the current study, multivariant traits were utilized to define 50 genotypes in the first year and 10 genotypes in the second year. The phenotypic correlations among all traits in the entire germplasm were assessed, and the data acquired for all quantitative characters were subjected to analysis of variance for augmented block design. Furthermore, the WINDOWS STAT statistical software was used to calculate Principal Component Analysis (PCA). The presence of substantial variations in most symptoms was shown by analysis of variance. GCV (Genotypic coefficient of variation) projections for grain yields were higher, followed by panicle lengths and organic yields. Plant height and leaf length had the highest PCV estimates, followed by leaf width. Low GCV and PCV (Phenotypic coefficient of variation) were measured as leaf length and 50% flowering in days. According to the PCV study, direct selection based on characters, panicle weight, test weight, and strawweight had a high and positive effect on grain yield per plant in both the rainy and summer seasons, indicating the true relationship between these characters and grain yield per plant, which aids indirect selection for these traits and thus improves grain yield per plant. Variability in foxtail millet germplasm enables plant breeders to effectively select appropriate donor lines for foxtail millet genetic improvement. Based on the average performance of genotypes considered superior in terms of grain yield components under Prayagraj agroclimatic conditions, the best 5 genotypes were found to be: Kangni-7 (GS-62)> Kangni-1 (G5-14), Kangni-6 (GS-55) Kangni-5 (GS-389) Kangni-4 (GS-368).